1976
DOI: 10.1128/jb.127.1.141-148.1976
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate dehydrogenase: genetic mapping and isolation of regulatory mutants of Klebsiella aerogenes

Abstract: The gene for glutamate dehydrogenase (gdhD) has been mapped in Klebsiella aerogenes by P1 transduction. It is linked to pyrF and trp with the order pyrF-trp-gdh. Complementation analysis using F' episomes from Escherichia coli suggests an analogous location in E. coli. Two mutants able to produce glutamate dehydrogenase in the presence of high levels of glutamine synthetase have been isolated. One, tightly linked to gdhD, shows normal repression control by glutamine synthetase but produces four times as much g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…cotransducible with the tyramine oxidase gene (tynA) (10). There are some reports that the map positions of genes in E. coli are similar to those of analogous genes in K. aerogenes (5,17). Complementation of a mutation in K. aerogenes by an episome derived from the E. coli chromosome ought, therefore, to be a useful method for locating the mutation on the K. aerogenes chromosome, although no genetic study on arylsulfatase and tyramine oxidase in E. coli has been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cotransducible with the tyramine oxidase gene (tynA) (10). There are some reports that the map positions of genes in E. coli are similar to those of analogous genes in K. aerogenes (5,17). Complementation of a mutation in K. aerogenes by an episome derived from the E. coli chromosome ought, therefore, to be a useful method for locating the mutation on the K. aerogenes chromosome, although no genetic study on arylsulfatase and tyramine oxidase in E. coli has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Scoring of the Ats and Tyn phenotypes was done as described previously (10), except that, when the transductants re(juired glutamine, the Tyn phenotype was scored by assay of tvramine oxidase in test tubes. Gdh and Pvr phenotypes were scored as described by Bender et al (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of several strains with mutations in the structural gene for GDH, gdhA, has demonstrated that the enzyme activity is not essential as long as glutamate synthase is functional (14,15,30). The regulation of ghdA in S. typhimurium differs from that in K. aerogenes, in which growth with a limiting nitrogen source causes a decrease in GDH activity (2,7), and from that in E. coli, where nitrogen limitation has no effect and only the supplementation of glucose-ammonia medium with glutamate causes a decrease in GDH activity (17,25,38). Thus, although similar biosynthetic routes to glutamate exist in a number of organisms, the pattern of gdhA regulation is unique for each.…”
mentioning
confidence: 99%
“…Mutants of E. coli (2, 20), K. aerogenes (1,13) and S. typhimurium (10) lacking glutamate synthase or glutamate dehydrogenase activity or both have been isolated, but it is not known whether these mutations identify structural genes or regulatory genes. The control of GDH in S. typhimurium is of particular interest because there is substantial expression of this enzyme activity in cells grown in a variety ofmedia, yet the enzyme appears to be unnecessary for growth (4,10).…”
mentioning
confidence: 99%